The Role Of Local Government In Tax Collection And Regional Retribution In DKI Jakarta Province - Fahrid, Fahrid; Raihan, Raihan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The Role of Local Governments in the Collection of Regional Taxes and Levies in DKI Jakarta Province Based on Law No. 1 of 2022 concerning Financial Relations Between the Central and Regional Governments.First, to find out and analyze the ability of local governments in collecting regional taxes and levies in DKI Jakarta Province and how the process of implementing the collection of Regional Taxes and levies. Second, the scope of research on the role of local governments in collecting regional taxes and levies in DKI Jakarta Province. The third research method is to use qualitative research methods that are normative. Fourth, Research Results that discuss about. Regions are authorized to manage national resources available in their territories and are responsible for maintaining environmental sustainability in accordance with the law. The authority of the Government in collecting taxes and regional levies has been determined by applicable laws and regulations, DKI Jakara tax revenues and levies. Fifth, the conclusion of the DKI Jakarta Regional Revenue Agency (Bapenda) recorded the realization of DKI Jakarta tax revenue from January to the end of June of Rp 22.35 trillion. This amount is equivalent to 42.79% of DKI Jakarta's 2023 tax revenue target of IDR 52.23 trillion. The realization of these revenues has increased compared to the same period in the previous year. In the same period in 2022, DKI Jakarta's tax revenue only reached IDR 14.42 trillion. The tax revenue of Rp 22.35 trillion came from 13 types of regional taxes and 3 types of regional levies.